A left bundle branch block activation sequence and ventricular pacing influence voltage amplitudes: an in vivo and in silico study. (23rd November 2018) - Nguyên, Uyên Châu; Potse, Mark; Vernooy, Kevin; Mafi-Rad, Masih; Heijman, Jordi; Caputo, Maria Luce; Conte, Giulio; Regoli, François; Krause, Rolf; Moccetti, Tiziano; Auricchio, Angelo; Prinzen, Frits W; et al.
Abstract: Aims: The aim of this study was to investigate the influence of the activation sequence on voltage amplitudes by evaluating regional voltage differences during a left bundle branch block (LBBB) activation sequence vs. a normal synchronous activation sequence and by evaluating pacing-induced voltage differences. Methods and results: Twenty-one patients and three computer models without scar were studied. Regional voltage amplitudes were evaluated in nine LBBB patients who underwent endocardial electro-anatomic mapping (EAM). Pacing-induced voltage differences were evaluated in 12 patients who underwent epicardial EAM during intrinsic rhythm and right ventricular (RV) pacing. Three computer models customized for LBBB patients were created. Changes in voltage amplitudes after an LBBB (intrinsic), a normal synchronous, an RV pacing, and a left ventricular pacing activation sequence were assessed in the computer models. Unipolar voltage amplitudes in patients were approximately 4.5 mV (4.4–4.7 mV, ∼33%) lower in the septum when compared with other segments. A normal synchronous activation sequence in the computer models normalized voltage amplitudes in the septum. Pacing-induced differences were larger in electrograms with higher voltage amplitudes during intrinsic rhythm and furthermore larger and more variable at the epicardium [mean absolute difference: 3.6–6.2 mV, 40–53% of intrinsic value; interquartile range (IQR) differences: 53–63% of intrinsic value] compared to the endocardium (mean absolute difference: 3.3–3.8 mV, 28–30% of intrinsic value; IQR differences: 37–40% of intrinsic value). Conclusion: In patients and computer models without scar, lower septal unipolar voltage amplitudes are exclusively associated with an LBBB activation sequence. Pacing substantially affects voltage amplitudes, particularly at the epicardium.